STUDENTS' PERCEPTION IN USING YOUTUBE VIDEO IN LEARNING SPEAKING AT UIN ALAUDDIN MAKASSAR - Fani Faradillah; Sitti Nurpahmi (Universitas islam Negeri Alauddin Makassar, 2022)
This research is aimed at students' perception in using YouTube video in Learning speaking at UIN Alauddin Makassar. In the modern era, there are a lot of online learning platforms. New technologies developed to make learning process easier. One of the examples of online learning platforms is using YouTube video. This research started with designing blue print questionnaire for students and validation checklist for experts. This research employed a quantitative research and design is survey,where the data obtained from the questionnaires and interview. The questionnaires by the researcher with using theories from some experts. There are Theory motivation by (Kreisen, 2009, p. 3); Theory of Attitude by (Latchanna, and Dagnew 2009); and theory of Interest by (Stempleski, 2002). The subject of this research was 85 students of English Education Department academic year 2019 at UIN Alauddin Makassar.The data was analyzed by using the frequencies of Likert Scale and mean score. The mean score of students’ perception on using YouTube video in Learning speaking was 4.4. Based on the finding and discussion of the research, the researcher proposed to provided recommendation especially for the Head of English Education Department to apply using YouTube video in Learning speaking in English Education Department.